Safety of Blood Flow Restricted Exercise in Hypertension: A Meta-Analysis and Systematic Review With Potential Applications in Orthopedic Care. Issue 2 (June 2018) - Wong, Marlon L.; Formiga, Magno F.; Owens, Johnny; Asken, Tristen; Cahalin, Lawrence P.
Abstract : Blood flow restricted (BFR) exercise has recently been promoted in the United States as a novel method to restore skeletal muscle strength and hypertrophy in primarily athletic and healthy populations. A specialized tourniquet restricts blood flow after which brief and intermittent exercise is performed with low to moderate loads of resistance. A hypertensive blood pressure (BP) response during BFR exercise has been identified as a potential adverse effect, which may be particularly concerning for patients who are hypertensive. Because of the possibility that a substantial proportion of older adults undergoing orthopedic surgery may have hypertension as well as the possibility of a hypertensive BP response from BFR exercise, we performed a comprehensive search for studies examining the acute and chronic BP response to BFR exercise in hypertensive subjects resulting in 6 studies with which a meta-analysis and systematic review were performed. The meta-analysis results found nonsignificant, slight increases in systolic BP and diastolic BP. The results of the systematic review found that BFR exercise seems to be safe in patients with hypertension with no adverse events reported in the 86 patients who participated in the 6 reviewed studies. The cardiovascular response to BFR exercise seems to vary depending on the muscle group being exercised as well as the method of BFR, but, in general, these measures are greater during BFR exercise compared with non-BFR exercise.